Corporate diversity and economic performance: The impact of market specialization - Capon, Noël; Hulbert, James M.; Farley, John U.; Martin, L. Elizabeth (Strategic Management Journal, 1988)
This papers introduces a market‐based typology of corporate strategy, which builds on previous typologies (Rumelt 1974, 1982). We argue that, because different markets require different skills for success, firms which concentrate in one market area (consumer or industrial), at given levels of diversification, should achieve superior performance. Empirical tests with a sample of manufacturing firms support this proposed relationship between diversification strategy and financial performance.